Pengaruh Current Ratio, Debt To Total Asset, Sales Growth Terhadap Return On Asset Setelah Diakuisisi Dan Struktur Kepemilikan Sebagai Pemoderasi - Sari, Nova Permata; Dr, Darmansyah; Murni, Yetty (Jurnal Ilmiah Professional Indonesia, 2018)
ABSTRACT          The purpose of this research is to know whether there is influence of Current Ratio, Debt to Total Asset, Sales Growth to Return On Asset after acquired and ownership structure as moderator. The research sample is the target acquisition companies listed on the BEI, amounting to 9 companies. The independent variable is Current Ratio, Debt to Total Asset, Sales Growth, while the dependent variable is ROA, the moderating variable is the ownership structure. Data collection techniques with documentation techniques, analysis techniques with Classic Assumption Test, Multiple Regression Equation, Test t, Test F and Coefficient of Determination. Data processing with SPSS Software 23.Result of research prove Current Ratio partially have positive and significant influence to ROA, Debt Total Asset have positive and not significant to ROA, Sales Growth have negative and significant influence to ROA. The ownership structure does not moderate the influence of Current Ratio on ROA and Sales Growth on ROA, whereas Debt to Total Asset is moderated by Ownership Structure on target acquisition companies registered in IDX for financial report period 2011 â 2016. Keywords : Current Ratio, Debt to Total Asset, Sales Growth, The ownership structure, ROA     ABSTRAK          Tujuan penelitian untuk mengetahui apakah ada pengaruh Current Ratio, Debt to Total Asset, Sales Growth terhadap Return On Asset setelah diakuisisi dan struktur kepemilikan sebagai pemoderasi. Sampel penelitian adalah perusahaan target akuisisi yang terdaftar di BEI, berjumlah 9 perusahaan. Variabel independen yaitu Current Ratio, Debt to Total Asset, Sales Growth, sedangkan variabel dependennya yaitu ROA, variabel moderasinya yaitu struktur kepemilikan. Teknik pengumpulan data dengan teknik dokumentasi, teknik analisis dengan Uji Asumsi Klasik, Persamaan Regresi Berganda, Uji t, Uji F dan Koefisien Determinasi. Pengolahan data dengan Software SPSS 23.Hasil penelitian membuktikan Current Ratio secara parsial berpengaruh positif dan signifikan terhadap ROA, Debt Total Asset berpengaruh positif dan tidak signifikan terhadap ROA, Sales Growth berpengaruh negatif dan signifikan terhadap ROA. Struktur kepemilikan tidak memoderasi pengaruh Current Ratio terhadap ROA dan Sales Growth terhadap ROA, sedangkan Debt to Total Asset dimoderasi oleh Struktur Kepemilikan pada perusahaan target akuisisi terdaftar di BEI periode laporan keuangan tahun 2011 â 2016. Keywords : Current Ratio, Debt to Total Asset, Sales Growth, Struktur Kepemilikan, ROA